Hyponatremia in Pulmonary Disease - Uray Maulana; Atma Gunawan (RSUD Dr. Saiful Anwar Province of East Java, 2026)
Hyponatremia is a decrease in blood sodium levels below 135 mEq/L. Sodium is essential for proper nerve and muscle function. Sodium disorders have traditionally been considered a marker of the severity of underlying disease, but increasing evidence suggests that these have detrimental effects on physiological function. Hyponatremia can occur due to various diseases, including lung diseases, which are lung cancer, chronic obstructive pulmonary disease (COPD), tuberculosis, pneumonia, cystic fibrosis (CF), and coronavirus disease 2019 (COVID-19). The most common causes associated with hyponatremia with it are SIDH, volume depletion (e.g., vomiting, diarrhea), anticancer therapy, diuretics, and decreased nutritional intake. Early detection and correction of hyponatremia can significantly improve patient outcomes, reduce morbidity and mortality, and enhance the quality of care.